Solid-state power controllers for protection of DC grids - Loh, Wen Jie (Nanyang Technological University, 2024)
In recent years, studies have indicated that the adoption of dc grids has emerged as a more effective option for integration into the electrical system, enhancing overall performance. However, a significant challenge faced by dc grids is the lack of current zero-crossing, which complicates fault isolation.